Using Wordwall.Net on Vocabulary Mastery Students at MTsN 1 ABDYA - Nurul Haviza; Zuhri Efendi (Syntax Idea)
The most important thing when learning a new language is to master a lot of the vocabulary of that language. The aim is to determine the impact of Wordwall.net on students' vocabulary mastery, and the results of this research can contribute to the development of education in the current digital era. This research used a quantitative method with a pre-experimental one-group pre-test and post-test design, the technique used was purposive sampling, the sample in this research was 30 class VII Digital students at MTs Negeri 1 Aceh Barat Daya. Data analysis in this study used the Statistical Package for Social Science (SPSS) with a normality test, paired difference test (paired sample t-test) and N gain Score test. Based on data analysis, the results of student scores in learning have criteria that are quite effective. Based on the t test output, the value obtained is sig = 0.001, which means it is smaller than 0.005. Therefore, the increase in scores from the pre-test to post-test is quite high. From the presentation of the results and discussion of the research, it can be concluded that the use of the wordwall.net platform in mastering digital understanding for class VII in English language learning is quite effective